Dietary Intake of Polyunsaturated Fatty Acids and Pain in Spite of Inflammatory Control Among Methotrexate‐Treated Early Rheumatoid Arthritis Patients. Issue 2 (29th January 2018) - Lourdudoss, Cecilia; Di Giuseppe, Daniela; Wolk, Alicja; Westerlind, Helga; Klareskog, Lars; Alfredsson, Lars; van Vollenhoven, Ronald F.; Lampa, Jon
Abstract : Objective: To investigate potential associations between dietary intake of polyunsaturated fatty acids (FAs) and pain patterns in early rheumatoid arthritis (RA) patients after 3 months of methotrexate (MTX) treatment. Methods: We included 591 early RA patients with MTX monotherapy from a population‐based prospective case–control study, the Epidemiological Investigation of Rheumatoid Arthritis. Dietary data on polyunsaturated FAs (food frequency questionnaires) were linked with data on unacceptable pain (visual analog scale [VAS] >40 mm), noninflammatory/refractory pain (VAS >40 mm and C‐reactive protein [CRP] level <10 mg/liter), and inflammatory pain (VAS >40 mm and CRP level >10 mg/liter) after 3 months. Statistical analysis included logistic regression. Results: After 3 months of MTX treatment, 125 patients (21.2%) had unacceptable pain, of which 92 patients had refractory pain, and 33 patients had inflammatory pain. Omega‐3 FA intake was inversely associated with unacceptable pain and refractory pain (odds ratio [OR] 0.57 [95% confidence interval (95% CI) 0.35–0.95] and OR 0.47 [95% CI 0.26–0.84], respectively). The omega‐6:omega‐3 FA ratio, but not omega‐6 FA alone, was directly associated with unacceptable pain and refractory pain (OR 1.70 [95% CI 1.03–2.82] and OR 2.33 [95% CI 1.28–4.24], respectively). Furthermore, polyunsaturated FAs were not associated with either inflammatory pain or CRP level and erythrocyte sedimentation rate at followup. Omega‐3 FA supplementation was not associated with any pain patterns. Conclusion: Omega‐3 FA was inversely associated with, and the omega‐6:omega‐3 FA ratio was directly associated with, unacceptable and refractory pain, but not with inflammatory pain or systemic inflammation. The inverse association between omega‐3 FA and refractory pain may have a role in pain suppression in RA.